Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - 11.4 - Complex Numbers - Problem Set 11.4: 44

Answer

$3-51i$

Work Step by Step

We multiply each term of the first complex number with the second complex number and then simplify: $(9-3i)(2-5i)$ =$9(2-5i)-3i(2-5i)$ =$18-45i-6i+15i^{2}$ =$18-51i+15(-1)$ [We substitute -1 in place of $i^{2}$ as $i^{2}=-1$] =$18-15-51i$ =$3-51i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.